2008
DOI: 10.2165/00019053-200826010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modelling of Infectious Diseases

Abstract: The indirect effect of vaccination on the non-vaccinated individuals (the 'herd immunity effect') can be greater than the direct effect on individuals vaccinated. This implies that the herd immunity effect needs to be taken into consideration in the economic evaluations of prophylactic measures employed against infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Supplementing these real-world observations, simulation studies on influenza frequently reported strong indirect effects: even relatively low vaccine coverage rates have been shown to yield important public health benefits in the US [5]. Indirect effects can even exceed direct effects [6]. Modeling studies of pediatric vaccination in the UK predicted more indirect than direct effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing these real-world observations, simulation studies on influenza frequently reported strong indirect effects: even relatively low vaccine coverage rates have been shown to yield important public health benefits in the US [5]. Indirect effects can even exceed direct effects [6]. Modeling studies of pediatric vaccination in the UK predicted more indirect than direct effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies reported data useful for the estimation of a mathematical function [13,19-25], 8 studies reported point estimate data on herd effect at a community level [11,23-29] and 8 studies in 9 publications reported point estimate data on herd effect in subpopulations [17,18,21,30-35]. These studies are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining six studies, two provided a graphical illustration [21,22], three reported data that allowed the estimation of a graphical illustration [23-25] and one provided other relevant data [13]. The studies included are described in more detail in Additional file 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations